Soil bioengineering for sustainable bioremediation of oil contaminated soils - Atai, Emmanuel (Cranfield University, 2022)
Contaminated soils arising from the petroleum industry remains a major problem globally, resulting in levels of petroleum hydrocarbons and metals that are dangerous to the environment. Modern remediation strategies focus on sustainability, thus maximizing environmental, social, and economic benefits. The use of materials derived from agricultural and industrial waste, for example biochar and spent mushroom compost (SMC), may provide a potential solution to sustainable remediation strategies. Biochar has numerous properties, e.g., high surface area and pore volume that may provide benefits to the remediation industry. SMC, a by-product of mushroom production, may contain diverse groups of microorganisms and extracellular enzymes important for the biotransformation of contaminants. Biochar and spent mushroom compost interactions in soil may induces diverse responses in microbial species leading to changes in soil enzyme activity, reshaping of microbial community structure and consequent enhancement of contaminants transformations. However, the mechanisms underlying these interactions are poorly understood, with unpredictable outcomes. There is a deficit of research designed to understand their collective response on soil fungi and the subsequent benefits to remediation success. Research needs to focus on the benefits of biochar towards affecting contaminant bioavailability of multiple rather than single contaminants. Combining biochar with SMC may facilitate the biodegradation of petroleum hydrocarbons in saline soils. The aim of the research was to develop a biotechnological approach for the best use of biochar and SMC to promote microbial remediation of soil contaminated with complex chemical mixture contaminants (hydrocarbons and heavy metals). It provides a mechanistic understanding of the physicochemical and biological parameters influencing the remediation approach. The study further sheds light into the influence of low carbon soil amendment on the behaviour and fate of heavy metal(loids) and petroleum hydrocarbons, and the underlying microbial community responses in a genuinely contaminated soil in a four-month microcosms study, and in crude oil and salt spiked soil in another four-month microcosms study.
Coulon, Frederic - Associate Supervisor
Keywords: hydrocarbon; metal; biochar; Spent mushroom compost; bioamendment; microbial community